Strategi untuk Menumbuhkan dan Mengembangkan Kemampuan Berpikir Kritis Peserta Didik di Era 5.0 - Prastiko, Mufti Nawang; Arifin, Imron; Ubaidillah, Aan Fardani (Proceedings Series of Educational Studies, 2024)
Abstract The ability of critical thinking among students is a crucial component in their lives. Through critical thinking skills, students can comprehend and understand information comprehensively or in-depth. This research aims to explore, identify, and explain general publication trends, methodological approaches used, and strategies to cultivate and develop students' critical thinking skills. This study employs Systematic Literature Review (SLR) following PRISMA guidelines to obtain articles relevant to the researched topic. First, the publication trend of articles began in 2004, 2007, 2010, 2012, 2017, 2018, 2016, 2019, 2020, 2021, and 2022, with the highest frequency of research conducted in the United States, Indonesia, and Brazil. Second, the methodology approaches from highest to lowest frequency of use are quantitative, qualitative, mixed methods, literature review, and research & development (R&D). Third, strategies to foster and enhance critical thinking skills are implemented using 10 types of strategies such as curriculum-integrated approaches with various components, Integrated training methods (simulations and critical thinking strategies), practical inquiry model, academic motivation, clinical simulation, flipped classroom, didactic approaches, DL & MKS, classroom debates, and reciprocal teaching strategy. Abstrak Kemampuan berpikir kritis peserta didik merupakan suatu komponen yang berperan penting di kehidupannya. Melalui kemampuan berpikir kritis, peserta didik dapat mengerti dan memahami informasi secara komprehensif atau mendalam. Penelitian ini mempunyai tujuan untuk mengeksplorasi, mengetahui, dan menjelaskan trend publikasi secara umum, pendekatan metodologi yang digunakan, dan strategi untuk menumbuhkan dan mengembangkan kemampuan berpikir kritis peserta didik. Penelitian ini menggunakan Sistematis Literature Review (SLR) dengan panduan PRISMA untuk mendapatkan artikel yang mempunyai relevansi dengan topik yang diiteliti. Pertama, trend publikasi artikel dimulai pada tahun 2004, 2007, 2010, 2012, 2017, 2018, 2016, 2019, 2020, 2021, dan 2022 serta negara dengan frekuensi tertinggi dalam melaksanakan penelitian adalah Amerika, Indonesia, an Brazil. Kedua, pendekatan metodologi yang mempunyai frekuensi tertinggi menuju terendah untuk digunakan adalah kuantitatif, kualitatif, mixed methods, literature review, dan research & development (R&D). Ketiga, strategi untuk menumbuhkan dan mengembangkan kemampuan berpikir kritis dilaksanakan dengan menggunakan 10 jenis strategi seperti strategi pendekatan kurikulum yang diintegrasikan dengan beragam komponen, Integrated training methods (simulations and critical thinking strategies), pratical inqury model, motivasi akademis, clinical simulation, flipped classroom, didactic approaches, DL & MKS, classroom debates, dan reciprocal teaching strategy.